Tingkat Kepatuhan dan Tantangan Pelaksanaan Reklamasi serta Pascatambang IUP OP Batu Andesit di Kabupaten OKU Timur - Oktaviano, Oktaviano; Eddy Ibrahim; Bochori, Bochori (Pusat riset dan Inovasi Nasional, 2026)
Mining of rocks, particularly andesite, in East OKU Regency provides significant economic contributions but generates environmental impacts that require rehabilitation through reclamation and post-mining management. This study aims to evaluate the compliance level of Production Operation Mining Business License (IUP OP) holders with these obligations and to identify challenges in their implementation. A descriptive quantitative and qualitative approach was employed, with primary data collected through interviews and field observations related to reclamation and post-mining plans, as well as the placement of guarantees. Secondary data included IUP licensing documents, legislation, and guidance letters from the Energy and Mineral Resources Office of South Sumatra Province. Quantitative analysis categorized compliance levels, while qualitative analysis examined challenges and guidance strategies. The results indicate variations in IUP OP holders’ compliance; some have prepared documentation and placed guarantees, but delays and lack of continuity were observed. Major challenges include profit-oriented approaches, limited technical and environmental understanding, and limited permit duration. Guidance strategies, supervision, guarantee management, provision of technical experts, and community empowerment proved essential. These findings have implications for enhancing compliance, sustainable post-mining planning, and responsible mining practices.